Georgia Architectural and Historic Properties Survey of Rural [240] Southern part of the county, Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [240] Southern part of the county, Valdosta, Ga. December 1980. A one story L-shaped plan with gabled tin roof with clapboard siding. Modern windows, interior chimney, brick piers. Fair condition. Date of Construction: c. 1910. A typical rural L-shaped plan common to these rural areas.
Georgia Architectural and Historic Properties Survey of Rural [240] Southern part of the county, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.23 MB (1,290,645 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)